All the way up?, all the way down?: from cognitive science to cognitive curriculum; What about the affective component? / ¿Todo el camino hasta arriba?, ¿todo el camino hasta abajo?: desde la ciencia cognitiva hasta el currículo cognitivo... - Raúl Montes de Oca Rodríguez (Universidad de Costa Rica, 2004)
This article is directed to English language teachers and / or students of teaching  English as a Foreign/Second  Language (EFL) (ESL) mainly, but readers from other disciplines are welcome aboard.  Its purpose is to present an overview of cognitive science in relation to language teaching and learning.  Areas like cognitive psychology, cognitive teaching and learning, and second language acquisition are explored  as part of the panorama that is portrayed.  The objectives are to briefly  delineate some visible historic points and remarkable features of cognitive science, and to relate these characteristics  to today`s language teaching and learning trends. The author´s proposal involves taking into account two areas  in ESL/EFL simultaneously: the cognitive and the affective, since the latter seems to be overlooked nowadays and more emphasis is being given to cognitive elements like learning strategies.  In the conclusion, the author insists on giving the development of eventual school or high school programs on self- esteem the same status as the designing of future learning strategies programs or the teaching /  training of learning strategies in relation to subjects like English.   Este artículo está dirigido a profesores de inglés y estudiantes de enseñanza del inglés como lengua extranjera o como segundo idioma (EFL) (ESL) principalmente, pero lectores de otras disciplinas son bienvenidos. El propósito del artículo es presentar una panorámica general de la ciencia cognoscitiva en relación con la enseñanza y aprendizaje de un idioma. Áreas como la psicología cognitiva, la enseñanza y el aprendizaje cognitivos, y la adquisición de un segundo idioma se incluyen como parte de lo que se quiere dar a conocer. Los objetivos son el delinear someramente algunos puntos visibles e importantes de la ciencia cognitiva y relacionarlos con las características de las tendencias en cuanto a enseñanza y aprendizaje de un idioma hoy en día. El autor propone tomar en cuenta dos áreas de ESL/EFL simultáneamente: la cognitiva y la afectiva, ya que esta última pareciera haberse dejado de lado últimamente, dándosele más énfasis a elementos cognitivos como las estrategias de aprendizaje. En la conclusión, el autor insiste en dar el mismo status al desarrollo eventual de ambos programas: a los del desarrollo de la autoestima y los de estrategias de aprendizaje que eventualmente se puedan estar diseñando tanto en escuelas como en colegios.